The Roles of Canadian Universities in Heterogeneous Third-Age Learning: A Call for Transformation - Ratsoy, Ginny R. (Canadian Journal of Higher Education, 2016)
This article makes the case that Canadian universities—both within and beyond their campuses—must broaden their visions of third-age learners. Canadian third-age learners—defined for the purposes of this article as persons seeking formalized education who are in the stage of life beginning at retirement—are more numerous, active, financially stable, and diverse as well as healthier and better educated than at any other time in our history. It follows that Canadian universities have much to offer and gain by both deepening and broadening their involvement with these learners. I argue that universities must consider multi-pronged forms of collaboration and must be motivated, at all times, not by short-sighted financial concerns but by their core obligation to serve the public good by fostering community engagement.